Multimodal hypoxia imaging and intensity modulated radiation therapy for unresectable non-small-cell lung cancer: the HIL trial - Askoxylakis, Vasileios; Dinkel, Julien; Eichinger, Monika; Strauss, Ludwig G.; Dimitrakopoulou-Strauss, Antonia; Kopp-Schneider, Annette; Haberkorn, Uwe; Huber, Peter E.; Bischof, Marc; Debus, Jürgen; Thieke, Christian (Radiation oncology, 2012)
BACKGROUND: Radiotherapy, preferably combined with chemotherapy, is the treatment standard for locally advanced, unresectable non-small cell lung cancer (NSCLC). The tumor response to different therapy protocols is variable, with hypoxia known to be a major factor that negatively influences treatment effectiveness. Visualisation of tumor hypoxia prior to the use of modern radiation therapy strategies, such as intensity modulated radiation therapy (IMRT), might allow optimized dose applications to the target volume, leading to improvement of therapy outcome. (18)F-fluoromisonidazole dynamic positron emission tomography and computed tomography ((18) F-FMISO dPET-CT) and functional magnetic resonance imaging (functional MRI) are attractive options for imaging tumor hypoxia. METHODS/DESIGN: The HIL trial is a single centre study combining multimodal hypoxia imaging with (18) F-FMISO dPET-CT and functional MRI, with intensity modulated radiation therapy (IMRT) in patients with inoperable stage III NSCLC. 15 patients will be recruited in the study. All patients undergo initial FDG PET-CT and serial (18) F-FMISO dPET-CT and functional MRI before treatment, at week 5 of radiotherapy and 6 weeks post treatment. Radiation therapy is performed as inversely planned IMRT based on 4D-CT. DISCUSSION: Primary objectives of the trial are to characterize the correlation of (18) F-FMISO dPET-CT and functional MRI for tumor hypoxia imaging in NSCLC and evaluate possible effects of radiation therapy on tumor re-oxygenation. Further objectives include the generation of data regarding the prognostic value of (18) F-FMISO dPET-CT and functional MRI for locoregional control, progression free survival and overall survival of NSCLC treated with IMRT, which will form the basis for larger clinical trials focusing on possible interactions between tumor oxygenation and radiotherapy outcome. TRIAL REGISTRATION: The ClinicalTrials.gov protocol ID is NCT01617980.